2021
DOI: 10.1111/iju.14489
|View full text |Cite
|
Sign up to set email alerts
|

Does cognitive behavioral therapy using a self‐check sheet improve night‐time frequency in patients with nocturia? Results of a multicenter randomized controlled trial

Abstract: To determine whether cognitive behavioral therapy using a self-check sheet is effective in improving night-time frequency of patients with nocturia. Methods: We carried out a multicenter, open-labeled, randomized controlled trial in eight institutions. Patients having two or more episodes of nocturia were randomly assigned to either cognitive behavioral therapy with completion of frequency volume charts regularly (cognitive behavioral therapy group) or frequency volume charts regularly alone (frequency volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…4 Desmopressin therapy is one of the main strategies against nocturia with NP, along with lifestyle modifications. 5,6 Cho et al have suggested that combining behavioral therapy with desmopressin increases the maximal bladder capacity and decreases the nocturnal polyuria index (NPI). 7 To prevent a unique side effect, hyponatremia, the International Continence Society suggested a practical algorithm before and after prescribing desmopressin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Desmopressin therapy is one of the main strategies against nocturia with NP, along with lifestyle modifications. 5,6 Cho et al have suggested that combining behavioral therapy with desmopressin increases the maximal bladder capacity and decreases the nocturnal polyuria index (NPI). 7 To prevent a unique side effect, hyponatremia, the International Continence Society suggested a practical algorithm before and after prescribing desmopressin.…”
Section: Introductionmentioning
confidence: 99%
“…Desmopressin therapy is one of the main strategies against nocturia with NP, along with lifestyle modifications 5,6 . Cho et al have suggested that combining behavioral therapy with desmopressin increases the maximal bladder capacity and decreases the nocturnal polyuria index (NPI) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Kincade et al [ 30 ] provided individualized counseling regarding self-monitoring techniques for adequate caffeine and fluid consumption and simple pelvic floor muscle training (PFMT). Kyoda et al [ 31 ] provided cognitive behavioral therapy (CBT), which included caffeine restriction and decreased water intake in the evening. Swithinbank et al [ 32 ] asked patients with urodynamic stress incontinence and idiopathic detrusor overactivity to restrict their caffeine intake for 3 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The G*power version 3.1.9.6 calculator (Franz Faul, Universität Kiel, Germany) was used for the statistical tests followed by the repeated measures analysis of variance (ANOVA) between factors, with alpha error of 0.05, power of 0.80, number of measurements 3, and effect size 0.5 (medium) [ 13 , 24 , 25 ]. Statistical analysis was performed using statistical software SPSS version 25 (IBM, Armonk, NY, USA).…”
Section: Methodsmentioning
confidence: 99%